Prinsip – Prinsip Pengembangan Kurikulum dalam Upaya Meningkatkan Kualitas Pembelajaran - Shofiyah Shofiyah (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2018)
Education occupies a very strategic position in realizing the process of maturity and human thinking. Given the importance of education for human life, education must be carried out as well as possible. To achieve the educational goals, a curriculum is needed as one of the tools and guidelines in achieving educational goals. The curriculum is a device that is inseparable from the operation of education itself, because the preparation of the curriculum is spelled out from certain educational theories. This means that the curriculum is seen as a concrete plan in the application of educational theory. In the development of an educational curriculum must follow the principles of curriculum development that are in harmony with human nature and directed to achieve the ultimate goal of education. The curriculum should pay attention to the periodization of the development of students and maintain the needs of the community and their organizations not contradictory and not cause conflict. Effective curriculum and curriculum that pay attention to the level of development of students. Curriculum development is one of the efforts made to achieve educational goals, one of which is to improve the quality of learning